The grand illusion : the prussianization of the Chilean Army - Sater, William F. (Studies in war, society, and the military., 1999)
"Well-researched and welcome work on the German efforts to train the Chilean army during the Parliamentary Regime (1891-1924). Argues convincingly that what appeared outwardly to be a Prussian-style military was in reality an ill-fed, poorly equipped military force rife with corruption and low on morale. Many of the German trainers, themselves, contributed to the malaise by seeking profits from weapons sales and land deals. Oddly, perhaps, the Chilean army continues to display the influences of the German era"--Handbook of Latin American Studies, v. 58.